2008
DOI: 10.1016/j.jcrs.2008.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment changes during accommodation in eyes with a monofocal intraocular lens: High-frequency ultrasound study

Abstract: Anterior segment structures demonstrated accommodative movement on UBM after implantation of standard monofocal IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
2
29
0
2
Order By: Relevance
“…Marchini et al 23 also showed accommodative movement on UBM after implantation of standard monofocal IOLs.…”
Section: Discussionmentioning
confidence: 91%
“…Marchini et al 23 also showed accommodative movement on UBM after implantation of standard monofocal IOLs.…”
Section: Discussionmentioning
confidence: 91%
“…To the best of our knowledge, this is the first report that describes the changes in ACA during accommodation (16) in subjects who underwent IOL implantation and whose mean age was 76 ± 6 years. After 3 D of accommodation, the ACA decreased by approximately 1.22 degrees at the horizontal meridian and by 0.75 degrees in the vertical direction.…”
Section: Anterior Chamber Anglementioning
confidence: 89%
“…Table 1 is a compilation of the results of all studies that evaluated at least one of these three eye metrics during accommodation. Studies assessing the changes in central ACD , mean ACA (16) , and PD (3,7,26,28,29) during accommodation concluded that these metrics decreased after increasing the stimulus vergence. Figure 1 The changes in the peripheral ACD and ACA at different meridians during accommodation have not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These movements influence the IOL position, which undergoes modification during accommodative stimuli. 32 It is known that with eye axial elongation, many structures of the eye happen to have accompanied change including ciliary body and posterior iris. However, a study of ciliary muscle morphologic changes with accommodation in vivo deduced that the ciliary muscle was not found to be attenuated in myopic subjects as would be predicted from stretching alone, in fact, no significant relationship between ciliary muscle thickness and refractive error was identified.…”
Section: Discussionmentioning
confidence: 99%